Causal Relationship Model of Environmental Education - Thiengkamol, Nongnapas (Richtmann Publishing, 2012)
Environmental education has been accepted and applied for encouraging the global citizens to take a responsiblepractice through their behavior changing in daily life activity. This might be an effective and rapid change to decrease thegreenhouse gases via the awareness raising, attitude and value adjusting, skill and participation increasing including realpractice in daily living. The populations will be undergraduate students of academic year 2011 of Mahasarakham University. TheMulti-stage random sampling was used to collect the sample for 450 undergraduate students from different faculties. Thequestionnaire was employed as instrument for data collecting. LISREL was used for model verification. Results illustrated thatconsidering on structural model confirmatory factors of Environmental Education (EE) was able to explain the variation ofendogenous factors of Psychological Trait (Trait) caused endogenous factor of Environmental Behaviors for Global WarmingAlleviation (BEH) with 82.0 percents. BEH = 0.29 TRAIT + 0.75 EE ……………………..(1)(R2 = 0.82)